AB0165 THE EUROPEAN REGISTRY ON OBSTETRIC ANTIPHOSPHOLIPID SYNDROME (EUROAPS): A SURVEY OF 1100 CONSECUTIVE CASES. (June 2019) - Esteve-Valverde, Enrique; Alijotas-Reig, Jaume; Ferrer-Oliveras, Raquel; Sáez-Comet, Luis; Belizna, Cristina; Ruffatti, Amelia; Tincani, Angela; Decarolis, Sara; Latino, Omar; Cervera, Ricard
Abstract : Background: The obstetric antiphospholipid syndrome (OAPS) is an autoimmune disease defined by the presence of obstetric complications related to antiphospholipid antibodies. EUROAPS project is the biggest published European registry on obstetric antiphospholipid syndrome and it is ongoing. Objectives: To analyse the clinical features, laboratory data and foetal-maternal outcomes, and follow them up on a cohort of 1100 women with obstetric antiphospholipid syndrome (OAPS). Methods: Thirty hospitals throughout Europe have collaborated to carry out this registry. Cases with obstetric complaints related to antiphospholipid antibodies (aPL) who tested positive for aPL at least twice were included prospectively and retrospectively. The eight-year survey results are reported. Results: 1100 women with 3653 episodes were included of which 2553 were historical and 1100 were latest episodes. All cases fulfilled the Sydney classification criteria. According to the laboratory categories: 29.2% were in category I, 35.7% in IIa, 22.4% in IIb and 12.7%) in IIc. Miscarriages appeared in 38.6% cases. Early preeclampsia and early foetal growth restriction appeared in 18.1% and 16.1%, respectively. Patients with recommended treatment had a good live-birth rate (85%), while patients with no treatment showed a poor birth rate (49.6%). Conclusion: In this series, recurrent miscarriage is the most frequent poor outcome. To avoid false-negative diagnoses, all laboratory category subsets were needed. OAPS cases have very good foetal-maternal outcomes when treated. Results suggest that we were able to improve our clinical practice to offer better treatment and outcomes to OAPS patients. References: [1] Cervera R, Piette JC, Font J, Khamashta MA, Shoenfeld Y, Camps MT, et al. Antiphospholipid syndrome: clinical and immunologic manifestations and patterns of disease expression in a cohort of 1, 000 patients. Arthritis Rheumatol 2002;46:1019–1027. [2] Miyakis S, Lockshin MD, Atsumi T, Branch DW, Brey RL, Cervera R, et al. International consensus statement on an update of the classification criteria for definite antiphospholipid syndrome (APS). J Thromb Haemost2006;4:295–306. [3] Esteve-Valverde E, Ferrer-Oliveras R, Alijotas-Reig J. Obstetric antiphospholipid syndrome. Rev Clin Esp2016;216:135–45. Acknowledgement: Elmina Lefkou, Gerard Espinosa, Sara Tabacco, Luca Marozio, Pier Luigi Meroni, Tania Melnychuk, V Canti, Vittorio Pengo, Beatrice Chighizola, Maria Gerosa, Elisa Picardo, Elisa Llurba, Arsene Mekinian, Bettina Toth, Katharina Bremme, Ariela Hoxha, Disclosure of Interests: Enrique Esteve-Valverde: None declared, Jaume Alijotas-Reig: None declared, Raquel Ferrer-Oliveras: None declared, Luis Sáez-Comet: None declared, Cristina Belizna: None declared, Amelia Ruffatti: None declared, Angela Tincani Consultant for: UCB, Pfizer, Abbvie, BMS, Sanofi, Roche, GSK, AlphaSigma, Lillly, Jannsen, Cellgene, Novartis, Sara DeCarolis: None declared, Omar Latino: None declared, Ricard Cervera: None declared